The Accidental Curriculum - Terrance Riley (Journal of the Assembly for Expanded Perspectives on Learning, 2002)
True learning—learning which results in some permanent cognitive change—is far too unpredictable to be controlled by format curricular designs. The formal curriculum of English studies is valuable largely as a stage setting for educational accidents.